Performance analysis of a MIMO optical wireless link with space time block code (STBC) - Islam, Md. Zahirul (BRAC University, 2014)
This project report submitted in partial fulfillment of the requirement for the degree of Master of Engineering in Electrical and Electronic Engineering, 2014.